The theory of preloading: A cognitive-behavioural motivational model - Jacob G. Sorbello; Grant J. Devilly (Harm Reduction Journal)
Abstract Preloading of alcohol and/or drugs before an event has been examined in the research literature for the past two decades. Despite the considerable interest and scrutiny on the behaviour, there are limited, if any, attempts to conceptualise a theoretical understanding of why people preload before an event. Here we propose a Theory of Preloading (TOP)—a general cognitive-behavioural motivational model for alcohol and drug preloading. This conceptualisation reviewed and borrowed relevant cognitive, motivational and behavioural constructs from previous models—i.e., the Motivational Model of Alcohol Use, (Cox & Klinger, 2011), PRIME theory (West, 2007); SORCK analysis (Kanfer & Sanslow, 1965)—applied to the target behaviour of preloading with alcohol and/or drugs. The TOP proposed that a central construct of affective management—guided by distal and cognitive factors—contributes to decisional factors for preloading. Consequential reinforcers and punishers create a reinforcement loop that feeds back into distal and immediate environmental factors for preloading, increasing the likelihood of future occurrences of preloading behaviours. Our proposed theoretical formulation concludes with practical and clinical implications, along with future directions for testing the model.